2018
DOI: 10.1002/ejp.1336
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of spinal cord stimulation for the treatment of pain: Still in the dark after 50 years

Abstract: Background and Objective Despite the value of spinal cord stimulation (SCS) in treating some patients with focal neuropathic pain, technological advances in stimulator design and treatment protocols have not correlated with significant improvements in clinical outcomes. This may be because incomplete understanding of the mechanisms underlying SCS precludes improvement in clinical efficacy. In this brief review, we (a) review phenomenological effects of SCS, (b) review the literature on proposed sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
77
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(94 citation statements)
references
References 71 publications
0
77
0
3
Order By: Relevance
“…The system also uses a three-dimensional finite element model to place a constant electrical field (dV/ dy) along the dorsal horn spanning one or more vertebral levels. A constant electrical field along the rostrocaudal plane of the spinal cord is hypothesized to selectively engage the synaptic terminals of rostrocaudally oriented inhibitory interneurons in the superficial dorsal horn [18,19]. Supporting this possibility are computational studies and experimental observations demonstrating that terminals may be preferentially polarized over axons of passage or cell bodies with near-field electrical stimulation using geometries designed to maximize the local electric field [20,21,22,23].…”
Section: Device Descriptionmentioning
confidence: 99%
“…The system also uses a three-dimensional finite element model to place a constant electrical field (dV/ dy) along the dorsal horn spanning one or more vertebral levels. A constant electrical field along the rostrocaudal plane of the spinal cord is hypothesized to selectively engage the synaptic terminals of rostrocaudally oriented inhibitory interneurons in the superficial dorsal horn [18,19]. Supporting this possibility are computational studies and experimental observations demonstrating that terminals may be preferentially polarized over axons of passage or cell bodies with near-field electrical stimulation using geometries designed to maximize the local electric field [20,21,22,23].…”
Section: Device Descriptionmentioning
confidence: 99%
“…Although this does not necessarily deliver more energy, currents applied for a longer time allow slow depolarizing ion channels in dendrites, cell bodies, and in lesser diameter and poorly myelinated axons to be excited (79). Also, a denser stimulation will recruit elements located deeper in the spinal cord (80), possibly including gray matter regions and projection fibers located in quadrants of the cord other than the dorsal columns (Figure 4A). Conversely, these parameters increase the chance of direct stimulation of nerve rootlets, which may cause discomfort in adjacent dermatomes or muscle contractions in correspondent myotomes (81).…”
Section: Translational Helix: Concepts From the Bench To The Bedsidementioning
confidence: 99%
“…Additionally, fMRI studies have demonstrated activation of cortical areas of the brain with SCS. Current evidence has been lacking to demonstrate if this is a top-down or a bottom-up effect and not all waveforms induce this physiologic response [7]. Our hypothesis is that cross-talk phenomena from the afferent effects of Nevro SCS caused a central inhibition of neuronal firing which leads the patient to develop transient tinnitus.…”
Section: Discussionmentioning
confidence: 92%
“…The precise mechanism of spinal cord stimulation has not been fully elucidated [2, 7]. Moreover, adverse neurologic effects of this therapy are not well known or understood.…”
Section: Introductionmentioning
confidence: 99%